Eggs and High Wall: What Psychotherapy Can Offer to Young People During Political Violence? A Hermeneutic Literature Review - Hui, Ka Lun Alan Fune (Auckland University of Technology, 2022)
Political violence can often be described as politically-motivated violence between non-system actors and a system, often asynchronous due to imbalances of power between system and non-system actors. Political violence often takes the forms of protest or active movements, and the younger generation is often the backbone of such movements (Afineevsky, 2015, Bristow, 2019, Castells, 2012, Ghonim, 2012, Jasper, 2004, Shirky, 2018, Sidney, 1994). Political violence can be seen as a type of collective trauma. Many research pieces have been dedicated to explaining and contributing to the literature about the use of psychotherapy to aid people who have suffered from trauma in the aftermath of political violence (Haen, 2018; Jackson & Seeman, 2009; Klavora & Korenjak, 2016; Kruse, Joksimovic, Cavka, Woller & Schmitz, 2009; Sexton, 2000). However, the use of psychotherapy during ongoing political unrest remains mostly unexplored. This study explores the phenomena and the use of psychotherapy during ongoing political violence. It is a hermeneutic phenomenological review of the literature, including online newspapers, TV and other media covering, and relating to, the 2019 Hong Kong Anti-Extradition Law Amendment Bill Movement, and explores the potential use and limitation of psychotherapy using psychoanalytic ideas. Focusing on Wilfred Bion’s ideas whose investigation of trauma and violence can shed some light on how psychotherapy can be used in situations of abnormality and ongoing violence.